Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1759720x20962623
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right treatment for patients with psoriatic arthritis

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory condition with articular and extra-articular manifestations: peripheral arthritis, axial disease, enthesitis, dactylitis, psoriasis, inflammatory bowel disease and uveitis. Anti-tumour necrosis factors (anti-TNFs) have demonstrated clinical efficacies exceeding those of conventional disease-modifying antirheumatic drugs (DMARDs). New understanding in pathogenic pathways have led to novel therapeutic targets. The current treatment paradigms emphasize early dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 109 publications
(162 reference statements)
0
7
0
2
Order By: Relevance
“…Several therapies are available for PsA with differing mechanisms of action, and treatment guidelines have focused on individualized treatment to address as many relevant disease domains as possible [ 2 , 4 , 5 ]. Conventional and biologic disease-modifying antirheumatic drug (DMARD) options for PsA include methotrexate and inhibitors of tumor necrosis factor, interleukin-17A (IL-17A), IL-12/23p40, IL-23p19, phosphodiesterase 4, T cell activation, and the Janus kinase pathway [ 1 , 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several therapies are available for PsA with differing mechanisms of action, and treatment guidelines have focused on individualized treatment to address as many relevant disease domains as possible [ 2 , 4 , 5 ]. Conventional and biologic disease-modifying antirheumatic drug (DMARD) options for PsA include methotrexate and inhibitors of tumor necrosis factor, interleukin-17A (IL-17A), IL-12/23p40, IL-23p19, phosphodiesterase 4, T cell activation, and the Janus kinase pathway [ 1 , 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is difficult to distinguish PsA from RA or osteoarthritis, because, in some cases, skin symptoms and arthritis develop simultaneously, and in other cases, arthritis precedes skin symptoms [ 40 ]. Since PsA is a disease that can cause serious damage to joints if diagnosis is delayed, a BM that can rapidly diagnose and predict the onset of PsA is required [ 42 , 61 ]. A previous report on PsA showed that the expression levels of high-sensitivity CRP, osteoprotegerin, MMP-3, and the ratio CPII of C2C differ between patients with psoriasis alone and those with PsA [ 62 ].…”
Section: Psoriasismentioning
confidence: 99%
“…The extra-articular manifestations of PsA include inflammatory bowel disease (IBD) and uveitis ( 5 ). In recent years, there are advancements in therapeutic options to treat musculoskeletal manifestations of PsA ( 6 ), but research to understand the pathogenesis of extra-articular manifestations and their treatment options is still in infancy. The purpose of this review is to summarize the current understanding of pathogenesis of PsA and the extra-articular manifestations and their treatment options.…”
Section: Introductionmentioning
confidence: 99%